Measuring efficieny of the start-up and the survival of undertakings in selected countries of the European Union over time using data envelopment analysis - Boďa, Martin
Posúdenie jednoduchosti a úspešnosti zakladania a prežitia podnikov v 21 členských štátoch Európskej únie.